SUKU MIGANI DAN NILAI-NILAI HIDUP KRISTIANI - Sondegau, Kleopas Sondegau (Studi Budaya Nusantara, 2018)
Abstract God's salvation mission for mankind has been carried out by Jesus Christ throughout life and work in this world. The Holy Spirit also animates the entire work of God's salvation so that the love of God displayed by Christ is increasingly experienced by human beings in a concrete way. Today the Catholic Church as its Mystical Body takes part in the mission of the Triune God for the salvation of mankind on this earth as well as the salvation of life in the afterlife. Thus, the Church continues to proclaim Christian values to all tribes including the Migani tribe. In the process of preaching the Church is certainly dealing with the context of local culture. This context will affect the pattern of the Church's preaching. Therefore inculturation efforts become very important because the Church realizes that every culture has positive values that deserve appreciation and then become a means of proclaiming Christian values. This paper will show a number of cultural values of the tribe of Migani who have sameness with Christian values in order to enrich each other so that their preaching is contextual.